Clinical and prognostic significance of elevated ferritin levels in hospitalised adults. Issue 1162 (12th April 2021) - Israel, Ariel; Bornstein, Gil; Gilad, Lee; Shechtman, Liran; Furie, Nadav; Ben-Zvi, Ilan; Grossman, Chagai
Abstract: Purpose of the study: Elevated ferritin levels are associated with a variety of infectious, malignant and inflammatory diseases. We aimed to investigate the prognostic value of markedly elevated ferritin levels in hospitalised patients with various medical conditions. Study design: Retrospective analysis of patients with a ferritin level higher than 2000 ng/mL hospitalised in Sheba Medical Center between 1 January 2007 and 31 December 2015. Medical conditions of these patients were recorded. In-hospital, 30-day and 1-year mortality rates were evaluated according to ferritin ranges and clinical categories. Results: The study included 722 patients (63.4% men) with a mean age of 63.9±16.7 years. The most common clinical conditions associated with markedly elevated ferritin were infectious diseases and malignancies. The highest mean ferritin levels were associated with rheumatological/inflammatory conditions (16 241.3 ng/dL), particularly in patients with macrophage activation syndrome (MAS) (96 615.5 ng/dL). In-hospital, 30-day and 1-year mortality rates were 32.3%, 46.7% and 70.8%, respectively. The highest in-hospital, 30-day and 1-year mortality rates were observed among patients with solid malignancies (40.1%, 64.7% and 90.3%, respectively), whereas the lowest rates were found among patients with rheumatological/inflammatory conditions, including MAS (21.4%, 38.1% and 45.2%, respectively). Ferritin levels were not associated with mortality. Conclusions: In hospitalised patients, ferritin levels higher than 2000 ng/mL are mainly associated with infectious and malignant diseases but do not predict mortality.